A high-resolution characterization of irradiation-assisted stress corrosion cracking of proton-irradiated 316L stainless steel in simulated pressurized water reactor primary water. (1st May 2022) - Kuang, Wenjun; Feng, Xingyu; Du, Donghai; Song, Miao; Wang, Mi; Was, Gary S.
Abstract: Irradiation-assisted stress corrosion cracks (IASCCs) from a proton-irradiated 316 L stainless steel (2.5 dpa) after constant load test in simulated PWR primary water were analyzed. The irradiation damages are consistent with those from neutron irradiations at similar dose. The IASCC cracks show microstructural and microchemical features similar to those reported from neutron-irradiated samples, confirming that proton is effective in emulating neutron for IASCC study. Si segregated at grain boundary gets oxidized preferentially beyond the crack tip and then dissolves into solution, resulting in enhanced porosity within the intergranular oxide. The Si effect is an important factor behind IASCC in reducing environment. Highlights: Proton irradiation induces similar IASCC features in SS as neutron irradiation. Intergranular oxidation is a necessary precursor of IASCC of SS at low doses. Si tends to get oxidized preferentially and dissolves during intergranular oxidation. The Si effect is likely a key element of IASCC mechanism for stainless steel.